profile
Опубликовано - 1 месяц назад | По предмету Математика | автор Аноним

Решите пример: (х+у - 4ху/х+у)*(у-х + 4ху/у-х)

  1. Ответ
    Ответ дан Пестов Ефим
    ((x + у) - 4xу/(x + у)) * ((у – x) + 4xу/(у – x)) = ((x + y)^2/(x + y) – 4xy/(x + y)) * ((y – x)^2/(y – x) + 4xy/(y – x)) =((x^2 + 2xy + y^2 – 4xy)/(x + y)) * ((y^2 – 2xy + x^2 + 4xy)/(y – x)) = ((x^2 - 2xy + y^2)/(x + y)) * ((y^2 + 2xy + x^2)/(y – x)) = ((x – y)^2/(x + y)) * ((y + x)^2/(y – x)) = ((y - x)^2/(x + y)) * ((x + y)^2/(y – x)) = (y – x) * (x + y) = y^2 – x^2.
    0